Pengolahan Ekoenzim dari Limbah Kulit Buah menjadi Pupuk Organik Cair dalam Mewujudkan Sektor Pertanian Rendah Karbon (Low-Carbon Agricultura) di Desa Konda Satu Kecamatan Konda Kabupaten Konawe Selatan - Gusnawaty HS; Rachmi Hariaty Hasan; Resman Resman; Suriana Suriana (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
The chemical dependency of farmers in Konda Satu Village and the accumulation of fruit peel waste potentially trigger greenhouse gas emissions. This Community Service (PKM) program aims to transfer science and technology in processing fruit peel waste into eco-enzyme as an environmentally friendly liquid organic fertilizer (POC). The implementation method was based on a participatory, educational, and applicative approach through socialization, direct technical guidance demonstrations, and field mentoring. The results of the activity showed a significant increase in community capacity, marked by more active participation in practicing eco-enzymes. This program also successfully compiled a practical guidebook and produced ready-to-use liquid fertilizer to stimulate a closed-loop agricultural system. In conclusion, this PKM activity has tangibly improved farmers' technical skills in processing waste into organic inputs toward low-carbon agriculture.